Postoperative results of laparoscopic lateral suspension operation: A clinical trials study - Aksin, Şerif; Andan, Cengiz (Frontiers in Surgery, 2023)
Postoperative results of laparoscopic lateral suspension operation: Clinical trials study Background: Pelvic organ prolapse surgery carries potential risks, and Laparoscopic lateral suspension (LLS) surgery is being performed in increasing numbers with advances in minimally invasive surgery. Our study aims to report the postoperative results of LLS operations. Patients and Methods: 41 patients at POP Q stage 2 and above underwent LLS operations in a tertiary center between 2017 and 2019. Postoperative patients 12 (12-37) months and older were evaluated in terms of anterior, apical, and posterior compartments. Results: In our study, laparoscopic lateral suspension (LLS) was applied to 41 patients. The mean age of all patients was 51.45 ± 11.51, and the operation time was 71.13 ± 18.70 minutes, The mean hospital stay was 1.35 ± 0.4 days. The apical compartment success rate was 78% and the anterior compartment success rate was 73%. In terms of patient satisfaction, 32 (78.1 %) patients were satisfied, While 37 (90.1%) patients did not have abdominal mesh pain, 4 (9.9%) patients had mesh pain. Dyspareunia was not observed. Conclusions: Laparoscopic lateral suspension in pop surgery; Considering the success rate below expectation, some patient groups can be applied as an alternative surgical method. Keywords: Laparoscopy, lateral suspension, prolapse uteri